METAVERSE: SHARIA CONTRACT LAW PERSPECTIVES - Muhammad Nur Ishak; Wahidin Musta’in Billah (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Abstract The Metaverse is a combination of reality and virtual reality, or the World. Through technology, the Metaverse combines augmented reality (AR) or augmented reality, a blend of 2D or 3D virtual objects into the real world in real-time, with virtual reality (VR), which can make simulations similar to the real world. Muslims should consider the impact and advantages of this technology because they already wear it daily. This paper studies and evaluates the halalness of the sharia commercial contract law in the Metaverse. This paper's qualitative analysis of sharia contracts uses the comparative descriptive method. Muslims should consider the impact and advantages of this technology because they already wear it daily. This paper studies and evaluates the halalness of the sharia commercial contract law in the Metaverse. This paper's qualitative analysis of sharia contracts uses the comparative descriptive method. Muslims should consider this technology's impact and benefits because they wear in real life. This study examines and analyzes sharia economic contract law in the Metaverse, looking at its halalness. These writings describe the fiqh, Koran, Hadith, and the opinions of scholars about the sharia contract in the Metaverse. The data used for comparison is found in the Metaverse. According to metaverse analysis, the perspective of the ijarah contract is the same as that of the metaverse transaction. In terms of losses, the payment of Crypto and NFTs in the Metaverse can be very dangerous for society, as their value is uncertain. Such transactions include gharar, which must be abandoned because they are doubtful and do not bring benefits, which is the purpose of Islamic law. Keywords: Islamic Law, Metaverse, Sharia Contracts.